Advances in magnetic-based thermometry and temperature mapping - Joana F Soeiro; Gabriela F Resende; Gabriel C Pinto; Nuno J O Silva (Physics in Medicine & Biology, 2026)
Abstract Temperature monitoring plays a critical role in a variety of therapeutic applications, including thermal therapies. Magnetic-based thermometry has emerged as a versatile and promising approach for localized, non-invasive temperature monitoring and mapping in vivo . This review provides an overview of the latest advances in magnetic temperature sensing techniques, with a focus on magnetic resonance imaging (MRI) and magnetic particle imaging (MPI). Established MRI thermometry techniques based on the variation of physical parameters with temperature are discussed, as well as the use of contrast agents to improve temperature sensitivity. In parallel, MPI-based thermometry is attracting growing interest as it combines quantitative imaging with the capacity to capture temperature-dependent changes of nanoparticle magnetization, offering high temporal resolution. Additionally, alternative magnetometry techniques with potential for temperature mapping are also considered. A comparative analysis highlights the strengths and limitations of these strategies and their suitability for clinical translation.